2010
DOI: 10.1111/j.1365-2702.2009.03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a lifestyle intervention among persons with a psychiatric disability: a cluster randomised controlled trail on symptoms, quality of life and sense of coherence

Abstract: Improving physical health with lifestyle programmes in the form of study circles and when involving their cares will in addition to increased physical health end in improved sense of coherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 52 publications
6
97
1
Order By: Relevance
“…We found great receptivity for this approach by clients themselves and by mental healthcare providers and administrators (Mesidor et al 2011) and modest evidence of its effect on perceived health status and functioning. These findings are similar to a small randomized study testing a lifestyle intervention program (Forsberg et al 2010).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found great receptivity for this approach by clients themselves and by mental healthcare providers and administrators (Mesidor et al 2011) and modest evidence of its effect on perceived health status and functioning. These findings are similar to a small randomized study testing a lifestyle intervention program (Forsberg et al 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Recently, interventions have been developed to address the physical health status of individuals with mental illness, some with a focus on increasing care integration, access to services, or the use of education to promote health awareness, self-care, and weight loss (Brown et al 2011;Daumit et al 2002;Dobscha and Ganzini 2001;Druss et al 2010b;Felker et al 1998;Forsberg et al 2010;Lindenmayer et al 2009). At the time this study was conducted, no research had tested the effectiveness of adding a nurse practitioner to improve health outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Health care professionals might be able to use information on patients' SOC to improve their HRQoL by concentrating on changing one or more of the three components of the SOC: comprehension, manageability and meaningfulness, not only during the hospitalisation but also during further recovery at home [18]. Furthermore, a significant increase in SOC could be gained by talk-therapy groups [52], social exchanges [53], mindfulness-based stress reduction programmes [54] and individualised psychoeducational programmes based on dialogue [55]. This could increase the self-care of patients with CHD and thus prevent the risk of recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…The SOC-13 has shown good acceptability among older people,44 has been used in several NH studies,26,45 and has shown high internal consistency in a review of 127 studies (Cronbach’s alpha ranges from 0.70 to 0.9244). The SOC-13 is a seven-point rating scale with two anchor responses: “never” and “very often”.…”
Section: Methodsmentioning
confidence: 99%